XML data integration in data warehouse system - Sahibuddin, Shamsul (2006)
The demand for data integration is rapidly becoming larger as more and more information sources appear in modern enterprises. Extensible Mark-up Language is fast becoming the new standard for data representation and exchange on the World Wide Web, e.g., in B2B and e-commerce, making it necessary for data analysis tools to handle XML data as well as traditional data formats. This research proposes an enhancement for data integration architecture and data integration approach for XML data and XML metadata. We are using a Common Warehouse Metamodel (CWM) for metadata interchange that incorporates a common shared metamodel to agree on metadata syntax and semantics. Analysis and evaluation had been done for concluded and summarized the new way for efficient and consistent data integration.